Pengembangan Masalah Matematika Berbobot (Rich Mathematical Task) untuk Meningkatkan Level Kemampuan Berpikir Siswa - Febrilia, Baiq Rika Ayu; Juliangkary, Eliska (Media Pendidikan Matematika, 2023)
The quality of learning mathematics in the classroom is influenced by the lesson plan that the teacher prepares long before the lesson is implemented, including the design of math assignments or problems. A task or problem should be able to encourage students to improve their thinking skills. One of the tasks that can encourage students to think at a higher level is rich mathematical tasks. The development of rich mathematical tasks is very important considering that these tasks can encourage students to think logically, creatively, innovatively, communicatively and evaluatively. This study aims to develop the design of rich mathematical tasks to increase the level of students’ thinking skills. The method used is development research which consists of three phases, namely the preliminary study phase, the development phase, and the final phase. However, this study is reported in the first two phases. The instruments used include prototype validation sheets and rich mathematical task question sheets. The results of this study are two problems that are developed, each of which is concentrated on the material of Three Variable Linear Equations System (SPLTV) and Comparison. This problem was then validated and obtained a score of 89.6%, which means that the problem is valid without needing to be revised. The try-out was carried out at partner schools involving 26 students in class XI IPA 1. The test results showed that the level of students’ thinking skills was still at the level of application, although there were some students who showed an analysis level.